MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN PAPER QUILING PADA ANAK USIA 5-6 TAHUN DI TK TUNAS PALMA KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Nisa’, Idza Khoirun; Zulkifli N, Zulkifli N; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of these research are: 1) To improve ability of fine motor in the children age 5-6 years old through paper quilling activities at the Tunas Palma Kindergarten Kerumutan Districts, 2) To know how to apply paper quilling in order to improve ability of fine motor for the children aged 5-6 years old at the Tunas Palma Kindergarten Kerumutan Districts, 3) To know the contribused of the influence of paper quilling activity to fine motor ability of the children age 5-6 years old at the Tunas Palma Kindergarten Kerumutan Districts. This form of research use Class room Action Research. Data collected is the by using observation sheet which consist of 7 indicators of fine motor ability. Based on the result of the research the indicated in every meeting cycle any incresing can be seen through of the result percentage of fine motor ability of the child, with the percentage value before the 39,097% cycle, the first is 50,56% cycle and the second is 77,19%. It can be seen from the improvement the data of the children, before the treatment the first cycle that is 29,31%, and then the first cycle to the scond cycle that is 52,67% an then before treatment to the second cycle that is 97,43%. The result based on the research is the paper quilling activity can incresing fine motor ability of the children age 5-6 years old at the Tunas Palma Kindergarten Kerumutan Districts. The improvement of the researc according of the expectations of the researcher made it in this study.Keywords: Fine Motor, paper quilling Activities